Regulating Reversible Oxygen Electrocatalysis by Built‐in Electric Field of Heterojunction Electrocatalyst with Modified d‐Band - He, Chaohui; Liu, Qingqing; Wang, Hongming; Xia, Chenfeng; Li, Fu‐Min; Guo, Wei; Xia, Bao Yu (Small (Weinheim an der Bergstrasse, Germany), 2023)
Developing bifunctional catalysts for oxygen electrochemical reactions is essential for high‐performance electrochemical energy devices. Here, a Mott–Schottky heterojunction composed of porous cobalt–nitrogen–carbon (Co‐N‐C) polyhedra containing abundant metal‐phosphides for reversible oxygen electrocatalysis is reported. As a demonstration, this catalyst shows excellent activity in the oxygen electrocatalysis and thus delivers outstanding performance in rechargeable zinc‐air batteries (ZABs). The built‐in electric field in the Mott–Schottky heterojunction can promote electron transfer in oxygen electrocatalysis. More importantly, an appropriate d‐band center of the heterojunction catalyst also endows oxygen intermediates with a balanced adsorption/desorption capability, thus enhancing oxygen electrocatalysis and consequently improving the performance of ZABs. The work demonstrates an important design principle for preparing efficient multifunctional catalysts in energy conversion technologies. The built‐in electric field and modified d‐band of the Mott–Schottky heterojunction electrocatalyst modulate the adsorption/desorption of oxygenate intermediates in reversible oxygen electrocatalysis.